DESKRIPSI KETERAMPILAN KOMUNIKASI SISWA KELAS VIII SMP NEGERI 17 PONTIANAK PADA MATERI ZAT ADITIF - Rosma Novianti; Masriani Masriani; Lukman Hadi (Universitas Tanjungpura, 2019)
Abstract The aims of this study was to describe students’ communication skills on topic of food additives. In order to achieve the aim, a descriptive study was conducted. A class of 29 students from 8th grade of SMPN 17 Pontianak participated in this study. It began with observation of activities during food additives class. The observation sheets were used to collect data of students’ communication skills. After class activities ended, a set of questions were asked to 10 students whom were selected randomly in order to obtain students’ response during previous class activities. Data were then analyzed descriptively. Results showed that students percentage score of verbal communication skills on asking, answering, and responding skills were 52.59 %, 24.14 %, and 17.24 % respectively and students percentage score of written communication skills on presenting data in table-form, writing a discussion, and writing a conclusion were 43.10 %, 56.90 %, and 44.83 % respectively. In conclusion, students’ verbal and written communication skills were 31.23 % and 48.28 % which were categorized as poor and good respectively. Keywords : Additives Compounds, Communication skils, Descriptive